2002
DOI: 10.1897/1551-5028(2002)021<0413:taopop>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxaphene and Other Persistent Organochlorine Pesticides in Three Species of Albatrosses From the North and South Pacific Ocean

Abstract: Toxaphene and other persistent organochlorine (OC) pesticides (chlordane-related compounds [CHL], DDT-related compounds [DDT], hexachlorocyclohexanes [HCH], tris(p-chloro-phenyl)methane, hexachlorobenzene, octachlorostyrene, diel-drin) were determined in fat of Laysan albatross (Diomedea immutabilis) and in fat and eggs of blackfooted albatross (Diomedea nigripes) from the central north Pacific Ocean. The HCH isomers and chlordane-and DDT-related compounds were also determined in eggs of northern royal albatro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 55 publications
2
20
1
Order By: Relevance
“…The compositions were basically the same over the period Oct 2000-Feb 2002, and relatively high concentrations were detected. Oxychlordane (26-34%) and transnonachlor (17-31%) were the major contributors to the overall CHL contamination, in agreement with results for albatrosses from the North Pacific Ocean (Muir et al, 2002). Although heptachlor epoxide (1.6-227 ng g -1 ) was found in all the samples, heptachlor was detected in the range 0.68-2.5 ng g -1 with a low frequency (17%).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The compositions were basically the same over the period Oct 2000-Feb 2002, and relatively high concentrations were detected. Oxychlordane (26-34%) and transnonachlor (17-31%) were the major contributors to the overall CHL contamination, in agreement with results for albatrosses from the North Pacific Ocean (Muir et al, 2002). Although heptachlor epoxide (1.6-227 ng g -1 ) was found in all the samples, heptachlor was detected in the range 0.68-2.5 ng g -1 with a low frequency (17%).…”
Section: Resultssupporting
confidence: 83%
“…These concentrations were considerably lower than those in Antarctic penguin fat (B8-1413, 34 ng g -1 ; B9-1679, 23 ng g -1 ) (Vetter et al, 2001). In this study, the ratio of [B8-1413]/[B9-1679] ranged from 1.1-2.9, contrasting with those (approximately 1.0) detected in albatrosses from the northern hemisphere (Muir et al, 2002). Although the reason for the dominance of B8-1413 was unclear, we expected that these ratio originated from feeding habits or differences among species.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…In Canada, PBDEs have been added to the List of Toxic Substances under Schedule 1 of the Canadian Environmental Protection Act (1999) and tetra-BDE, penta-BDE and hexa-BDE have been targeted for virtual elimination [28]. Toxaphene levels in heron eggs in the present study were higher than in Canadian Arctic seabirds [29], great egret (Ardea alba), and black-crowned night herons (Nycticorax nycticorax) from the Rio Grande Valley, but lower than in green heron (Butorides virescens) eggs from the Rio Grande Valley [30] and blackfooted albatross (Diomedea nigripes) eggs from the south Pacific Ocean [31]. Mean toxaphene levels of 300 ng/g wet weight were reported in great blue heron eggs from Indiana [32], compared to a mean of 54 ng/g wet weight in great blue heron eggs from the St. Lawrence River.…”
Section: Discussionmentioning
confidence: 66%
“…Verreault et al [34] found that congeners B8-1412, B8-2229 (Parlar 44), and B9-1679 (Parlar 50) predominated in glaucous gull eggs from the Norwegian arctic. Toxaphene is a persistent OC pesticide that has been widely used in the world until its ban in 1982 in Canada and the United States, and in the early 1990s in Mexico and elsewhere [31]. It has rarely been measured in birds, mainly because of difficulties involved in quantifying this multicomponent mixture [15,33].…”
Section: Discussionmentioning
confidence: 99%